2001
DOI: 10.1046/j.1365-313x.2001.01181.x
|View full text |Cite
|
Sign up to set email alerts
|

Local expression of enzymatically active class I β‐1, 3‐glucanase enhances symptoms of TMV infection in tobacco

Abstract: SummaryMutant tobacco plants de®cient for class I b-1,3-glucanase (GLU I) are decreased in their susceptibility to virus infection. This is correlated with delayed virus spread, a reduction in the size exclusion limit of plasmodesmata and increased cell-wall deposition of the b-1,3-glucan callose. To further investigate a role of GLU I during cell-to-cell movement of virus infection, we inserted the GLU I coding sequence into TMV for overexpression in infected cells. Compared with the size of local lesions pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
84
0
8

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(108 citation statements)
references
References 35 publications
7
84
0
8
Order By: Relevance
“…Many studies have confirmed that the b-1,3-glucanases play a role in mechanism involved in resistance to pathogenic infection, which are coordinately induced in response to pathogenic infection and it can be considered as pathogenesis-related protein of tobacco [28][29][30][31][32]. Our results demonstrated that that the activity of b-1,3-glucanases obviously increased in the presence of NNM (Fig.…”
Section: Discussionsupporting
confidence: 75%
“…Many studies have confirmed that the b-1,3-glucanases play a role in mechanism involved in resistance to pathogenic infection, which are coordinately induced in response to pathogenic infection and it can be considered as pathogenesis-related protein of tobacco [28][29][30][31][32]. Our results demonstrated that that the activity of b-1,3-glucanases obviously increased in the presence of NNM (Fig.…”
Section: Discussionsupporting
confidence: 75%
“…As described above, a period of 1-2 h is required for passage of VMCs; this need may indicate that biochemical changes, which cause temporary changes in size exclusion limits of the plasmodesmata (48), take place during this period. Other workers have shown that ␤-1,3 glucanase plays a role in controlling cell-cell spread of infection by TMV (49,50). We propose that activity of this enzyme and͞or other host proteins during the period that VRCs are tightly appressed to plasmodesmata, are important, if not essential, for cell-cell spread of the VMCs.…”
Section: Discussionmentioning
confidence: 66%
“…These processes occur upon the interaction between the virus and host proteins or after the suppression of the host basal defense mechanism and often lead to abnormal phenotypes of virus-infected host plants, such as small, highly branched bushes with deformed leaves, stunting, and reduced apical dominance (2)(3)(4). Thus, the reduced growth and developmental changes in the virus-infected plants are typical symptoms of virus infection and signify that the virus has undergone a successful life cycle.…”
mentioning
confidence: 99%